Membangun Ketahanan Pemuda berbasis Modal Sosial dalam Mencegah Penyalahgunaan Narkotika: Studi Tiga SMA di Jakarta Selatan - Pamungkas, Ghufron Irfandi; Puspitasari, Maria (Universitas Tribhuwana Tunggadewi, 2025)
This research is based on the high rate of drug abuse among young people. The high rate of abuse has an impact on the vulnerability of the community in terms of social, economic and health. This research aims to identify the forms of social capital that contribute to young people's resilience, by focusing on several youth communities in the South Jakarta area. Using the social capital theory proposed by Robert D. Putnam, this research explores the role of norms, social networks and trust in creating a supportive environment for drug abuse prevention through a qualitative approach with descriptive analysis techniques. Data collection techniques used interviews and document studies. Interviews were conducted with teacher and student from three senior high schools in South Jakarta. The results showed that the anti-narcotics norms socialized by schools through cooperation with BNN can help build students' collective awareness. To form social capital that contributes to young people's resilience is not easy. It requires a process through the social network support that BNN builds with schools through extracurricular activities and student council involvement and the group communication built through it. This is a form of emotional support that can prevent young people from getting involved with drugs. Positive meanings through communication between teachers and students, students and other students, both interpersonal communication and routine and intensive group communication in social networks contribute to the formation of social capital that can build young people's resilience to drugs.Penelitian ini didasari oleh tingginya angka penyalahgunaan narkotika di kalangan orang muda. Tingginya angka penyalahgunaan berdampak pada kerentanan masyarakat dari segi sosial, ekonomi dan kesehatan. Penelitian ini bertujuan untuk mengidentifikasi bentuk-bentuk modal sosial yang berkontribusi pada ketahanan orang muda, dengan memusatkan perhatian pada beberapa komunitas remaja di kawasan Jakarta Selatan. Dengan menggunakan teori modal sosial yang dikemukakan oleh Robert Putnam, penelitian ini mengeksplorasi peran norma, jaringan sosial dan kepercayaan dalam menciptakan lingkungan yang mendukung pencegahan penyalahgunaan narkotika melalui pendekatan kualitatif dengan teknik analisis deskriptif. Teknik pengumpulan data menggunakan wawancara dan studi dokumen. Wawancara dilakukan kepada guru dan siswa dari tiga SMA di Jakarta Selatan. Hasil penelitian menunjukkan bahwa norma antinarkotika yang disosialisasikan sekolah melalui kerja sama dengan BNN dapat membantu membangun kesadaran kolektif siswa. Untuk membentuk modal sosial yang berkontribusi pada ketahanan orang muda, tidak mudah. Membutuhkan proses melalui dukungan jaringan sosial yang dibangun BNN dengan sekolah melalui kegiatan ekstrakurikuler dan keterlibatan OSIS serta komunikasi kelompok yang dibangun melaluinya. Hal tersebut menjadi bentuk dukungan emosional yang dapat mencegah orang muda untuk terlibat dengan narkotika. Pemaknaan yang positif melalui komunikasi guru dengan siswa, siswa dengan siswa lainnya baik komunikasi interpersonal maupun komunikasi kelompok yang rutin dan intensif dalam jaringan sosial berkontribusi kepada terbentuknya modal sosial yang dapat membangun ketahanan orang muda terhadap narkotika.